2008
DOI: 10.1098/rsif.2007.1349
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of bird targets with radar via patterns produced by wing flapping

Abstract: Bird identification with radar is important for bird migration research, environmental impact assessments (e.g. wind farms), aircraft security and radar meteorology. In a study on bird migration, radar signals from birds, insects and ground clutter were recorded. Signals from birds show a typical pattern due to wing flapping. The data were labelled by experts into the four classes BIRD, INSECT, CLUTTER and UFO (unidentifiable signals). We present a classification algorithm aimed at automatic recognition of bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 37 publications
0
84
0
Order By: Relevance
“…In birds, the echo signature mirrors their wingbeat pattern (Bruderer, 1969;Bruderer, 1997) whereas in insects the complicated structure of the echo signature consists probably of a mixture of wing and other body movements (Schmaljohann et al, 2008a;Zaugg et al, 2008). Bird echoes can be assigned to groups of different flight styles according to their wingbeat pattern (Bruderer, 1969;Bruderer, 1997;Schmaljohann et al, 2008a;Zaugg et al, 2008): (a) continuously flapping flyers (waders, waterbirds, gulls, terns, rails, etc.…”
Section: Flight Stylesmentioning
confidence: 99%
See 2 more Smart Citations
“…In birds, the echo signature mirrors their wingbeat pattern (Bruderer, 1969;Bruderer, 1997) whereas in insects the complicated structure of the echo signature consists probably of a mixture of wing and other body movements (Schmaljohann et al, 2008a;Zaugg et al, 2008). Bird echoes can be assigned to groups of different flight styles according to their wingbeat pattern (Bruderer, 1969;Bruderer, 1997;Schmaljohann et al, 2008a;Zaugg et al, 2008): (a) continuously flapping flyers (waders, waterbirds, gulls, terns, rails, etc.…”
Section: Flight Stylesmentioning
confidence: 99%
“…With the tracking radar 'Superfledermaus' we recorded the echo signature of birds, i.e. the temporal variation of energy reflected by the bird (Schmaljohann et al, 2008a;Zaugg et al, 2008). This variation in the received signal mirrored the wingbeat pattern of the bird and can, therefore, be used for echo identification (Houghton, 1969;Bruderer and Joss, 1969;Bruderer, 1997;Schmaljohann et al, 2008a;Zaugg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Doppler radar data, insect echoes are a passive tracer for air motion. However, birds/bats have different Doppler velocity characteristics from wind fields [32][33][34]. Zhang et al [35] and Liu et al [36] identified the velocity contamination of migrating birds for WSR-88D radars.…”
Section: Review Of Polarimetric Signatures Of Clutter Echoesmentioning
confidence: 99%
“…Examples include detection and classification of people when walking [28][29][30], finding the number of people present in the environment from their heartbeat patterns [31], distinguishing human from four legged animals [32], classification of different species by physiological characteristics [33]. Radar has been used to retrieve continuous spatio-temporal data on bird migration [34,35], and to retrieve birds' flying characteristics such as height, velocity, direction, and density regardless of the time of fly.…”
Section: Discussionmentioning
confidence: 99%